EFFECTS OF SUBSTITUTION OF CEMENT WITH GROUND GRANULATED SLAG ON CONCRETE PRODUCED WITH DIFFERENT WATER-CEMENT RATIOS (Nigerian Journal of Technology, 2024)
Due to growing concerns on the need for alternative material to partially replace cement considering the  high cost and environmental problems associated with its production, this study investigated the impacts of fractional substitution of cement with ground granulated steel slag (GGSS) on the features of concrete produced by varying water-cement ratios (w/c). Cement was replaced with GGSS at 0, 10, 20, 30, 40, and 50%. The binder, sand and granite ratio of 1:2:4 as well as the w/c of 0.3, 0.4, 0.5, 0.6, and 0.7 were used. The X-ray fluorescence (XRF) analyser was utilized to ascertain the chemical composition of the GGSS, and its result revealed that GGSS is a class F Pozzolan. The fresh and hardened concretes containing various levels of replacement of cement with GGSS and w/c were subjected to workability and various strength tests. Response Surface Method (RSM) was employed for optimum condition analysis that maximized the results of the Compressive Strength (CS), Split Tensile Strength (STS) and Flexural Strength (FS) tests. Findings revealed that concrete becomes more workable with increasing w/c, but declined as the substitution of cement with GGSS increased. The strengths of the concrete declined with increasing w/c; however, the addition of GGSS improved its strength’s properties. The optimized 21.57% GGSS substitution for cement with w/c of 0.45 gave maximum value of 25.95 N/mm2 for  CS, 4.24 N/mm2 for  STS and 5.74 N/mm2for FS. The comparative cost analysis between the conventional concrete and the optimized OPC-GGSS concrete shows that as much as 11.2% of the concrete constituents’ cost can be saved if GGSS is used to substitute OPC in the concrete production. The optimized concrete, which can be utilized as reinforced concrete with improved strength and reduced cost, is therefore recommended for use with the target CS of 25 N/mm2.